Implementation of The Sima'i Method in Improving Memory of Daily Prayers - Priyono Priyono; Ibnu Fiqhan Muslim; Sanudin Ranam (Al-Hayat: Journal of Islamic Education, 2019)
In religious learning, students are expected to be able to understand the daily prayers taught in class. To achieve these goals, the right method is needed so students can follow these prayers. One way that can be used to prepare daily prayers is the sima'i method. This type of research is classroom action research. The results in this study are students can memorize correctly and both on the accuracy of speech, fluency, and attitude. This study concludes that the sima'i method has a positive influence on increasing the ability to memorize daily prayers on the subject. The results are taken based on the comparison of data between before and after being given treatment in the form of applying the sima'i method to the topic. Dalam pembelajaran agama, siswa diharapkan mampu mamahami doa-doa harian yang diajarkan di kelas. Untuk mencapai tujuan tersebut, diperlukan metode yang tepat agar siswa dapat memahami doa-doa tersebut. Salah satu metode yang dapat digunakan untuk mengajarkan doa-doa harian adalah metode sima’i. Jenis penelitian ini adalah penelitian tindakan kelas. Hasil dalam penelitian ini adalah siswa-siswa dapat menghafal dengan benar dan baik pada ketepatan ucapan, kelancaran dan sikap. Simpulan penelitian ini adalah metode sima’i memberikan pengaruh positif terhadap peningkatan kemampuan menghafal doa-doa harian pada subjek. Hasil tersebut diambil berdasarkan perbandingan data antara sebelum dan sesudah diberikan perlakuan berupa penerapan metode sima’i pada subjek.